Evolution and Structural Characteristics of Plant Voltage-Gated K+ Channels. Issue 12 (1st November 2018) - Jegla, Timothy; Busey, Gregory; Assmann, Sarah M.
Abstract: Plant voltage-gated K + channels have been referred to as "plant Shakers" in reference to animal Shaker channels, the first K + channels identified. Recent advances in our knowledge of K + channel evolution and structure have significantly deepened the divide between these plant and animal K + channels, suggesting that it is time to completely retire the "plant Shaker" designation. Evolutionary genomics reveals that plant voltage-gated K + channels and metazoan Shakers derive from distinct prokaryotic ancestors. The plant channels belong to a lineage that includes cyclic nucleotide-gated channels and metazoan ether-à-go-go and hyperpolarization-activated, cyclic nucleotide-gated channels. We refer to this lineage as the CNBD channel superfamily, because all these channels share a cytoplasmic gating domain homologous to cyclic nucleotide binding domains. The first structures of CNBD superfamily channels reveal marked differences in coupling between the voltage sensor and ion-conducting pore relative to metazoan Shaker channels. Viewing plant voltage-gated K + channel function through the lens of CNBD superfamily structures should lead to insights into how these channels are regulated.